ESTUDOS DE TRADUÇÃO E SEMIOLOGIA: AS CONTRIBUIÇÕES DE UMBERTO ECO - Gonçalves, Fabiano Bruno (Organon, 2004)
By exposing the reflections on interpretation and translation by the Italian semiologist and novelistUmberto Eco, we intend to make it clear that his ideas and theories are of great value to any current reflectionon translation – mainly literary translation. Albeit chiefly based upon linguistics, the semiologist’s ideas areloaded with a wide range of knowledge from many fields, which only contributes to a firmly based “theory” oftranslation.